If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3(2n+5)-3n=2(n+5)-3(2n-4)
We simplify the equation to the form, which is simple to understand
3(2n+5)-3n=2(n+5)-3(2n-4)
Reorder the terms in parentheses
+(+6n+15)-3n=2*(n+5)-3*(2n-4)
Remove unnecessary parentheses
+6n+15-3n=+2+*(+n+5+)-3+*(+2n-4+)
Reorder the terms in parentheses
+6n+15-3n=+(+2n+10)-3*(2n-4)
Remove unnecessary parentheses
+6n+15-3n=+2n+10-3+*(+2n-4+)
Reorder the terms in parentheses
+6n+15-3n=+2n+10+(-6n+12)
Remove unnecessary parentheses
+6n+15-3n=+2n+10-6n+12
We move all terms containing n to the left and all other terms to the right.
+6n-3n-2n+6n=+10+12-15
We simplify left and right side of the equation.
+7n=+7
We divide both sides of the equation by 7 to get n.
n=1
| 3y^2-51y+90= | | 2d-3+3c-2d-3+3c=4d-12+6c | | -x-16=-5x | | y=-2.7x^2+30x+6.5 | | 93.96=4.7p+8.79p-2.6p | | 3(x+2)=9x+1-6x+5 | | -4(-5x-4)=-44 | | x-.3x=200 | | 5.1-x=20.3 | | .25(-8x+8)=-2+2x | | x^2-13x*y+40y^2=0 | | 2(7d-6)+8= | | lx+2l=-lx-2l | | 50-10(4-2)+6= | | 0.56x-0.86=11.35-2.74x | | -5x+12=-3x-6 | | .25(-8x-8x)=-2+2x | | 4(x+6)=3x-2 | | 5x+12=-3x-6 | | -7(x+4)-45=5-22 | | -14+x=x+29 | | 3y=3(6.68)-3 | | .25(-x+8)=-2+2x | | 12=5y-25 | | 7n+14=-2n+50 | | 8a+5c=3369 | | 6x-1-3=4 | | 0.5+0.25=2.00 | | Ln(x+3)+Ln(2)=Ln(16) | | ln(30x)=y | | lx+2l+lx-2l=0 | | 1/2x+6=1/6 |